2021
DOI: 10.21744/lingcure.v5ns1.1401
|View full text |Cite
|
Sign up to set email alerts
|

Why English teaching truth on digital trends as an effort for effective learning and evaluation: opportunities and challenges: analysis of teaching English

Abstract: This study aims to gain a comprehensive understanding of why foreign language teaching, especially English, believes in using digital trend applications to improve learning effectiveness and evaluation validity in the perspective of current opportunities and challenges. So, for this purpose, the step we take is to examine hundreds of scientific reports on teaching English in many international contexts to answer the questions above with valid and reliable principles. Because Indonesia is currently in the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 42 publications
1
34
0
3
Order By: Relevance
“…e literature [13] proved that indirect feedback is more effective; the literature [14] did not find a significant difference in the effectiveness of the two forms of feedback; and the literature [15] confirmed that direct feedback is more dominant. Considering that the previous experimental methods are not rigorous enough, the literature [16] conducted two more rigorous experiments: the results show that both direct and indirect corrective feedback can significantly improve learners' writing accuracy, and the effect of direct feedback is less. It is better than the indirect effect, because the effect of direct feedback can maintain a certain continuity, while indirect feedback cannot.…”
Section: Related Workmentioning
confidence: 99%
“…e literature [13] proved that indirect feedback is more effective; the literature [14] did not find a significant difference in the effectiveness of the two forms of feedback; and the literature [15] confirmed that direct feedback is more dominant. Considering that the previous experimental methods are not rigorous enough, the literature [16] conducted two more rigorous experiments: the results show that both direct and indirect corrective feedback can significantly improve learners' writing accuracy, and the effect of direct feedback is less. It is better than the indirect effect, because the effect of direct feedback can maintain a certain continuity, while indirect feedback cannot.…”
Section: Related Workmentioning
confidence: 99%
“…Artificial intelligence technology has a good international influence, but there are still gaps between countries. Artificial intelligence courses refer to courses that are supported by artificial intelligence technology and conduct research on its principles, methods, and applications [ 2 ]. At present, the scope of research in the field of artificial intelligence continues to expand, not only in common robotics, image, and language recognition technologies but also in natural language processing and expert systems.…”
Section: Introductionmentioning
confidence: 99%
“…In teaching practice, interactive education attaches great importance to mutual help and encouragement among student groups. erefore, teachers should help students understand important knowledge points and exibly use the understanding ability of the student group to connect them with new knowledge points [2]. Also, the conversation must have a purpose and direction so that students and teachers understand classroom goals.…”
Section: Introductionmentioning
confidence: 99%